Pengaruh Gaji, Stres Kerja, dan Keadilan Interaksional terhadap Perilaku Penyimpangan Pegawai (Employee Deviance) Studi Kasus terhadap Divisi Marketing PT. XYZ - Deni Wardani; Yousef Yousef (STIE Indonesia Banking School, 2016)
With the high expectation towards quality human resouce. This research was conducted to identify the effect of Wage Compensation, Interactional Justice and Job Stres towards Employee Deviance. The object of this research is PT. XYZ which is one of the most respectable company in Indonesia. This research is a quantitative descriptive research. There were 149 respondents of XYZ’s Marketing Division which were gathered by convenience sampling. The results showed that Wage Compensation, Job Stres, and Interactional Justice has a significant effect towards Employee Deviance.